Project Budgeting at a Company - Antadin, Norman (International Publisher, 2022)
The author made this study entitled Budgeting at CV Bima Cahaya Dotia. The purpose of this final assignment is to find out how to prepare the budget at CV Bima Cahaya Dotia, to find out how to prepare the sales budget at CV Bima Cahaya Dotia, to find out how to prepare the cash receipts budget at CV Bima Cahaya Dotia, to find out how to prepare the budget at CV Bima Cahaya Dotia, and to find out how to prepare profit and loss at CV Bima Cahaya Dotia. The research method used is a qualitative method by taking data directly from companies or institutions and the data taken is done by observation and interviews. So it can be concluded that the preparation of the budget at CV Bima Cahaya Dotia uses data from last year's period, and budget increases are decided by the director and approved by managers